Workplaces Spirituality Towards Leadership Effectiveness - Ismail, Fadillah; Saimy, Intan Sazrina; Mohd Rosli, Nur Amalina; Mansor, Nisha Naderra (Online Journal for TVET Practitioners, 2019)
In Malaysia, the research about workplace spirituality towards leadership effectiveness is rarely done. The workplace spirituality indicates the meaningful work, sense of community and alignment of values. The purpose of this study is to determine the relationship between workplace spirituality towards leadership effectiveness. There were three hypotheses that had been examined; meaningful works, sense of community and alignment of values. The research has been conducted to the volunteers at Civil Defense, Batu Pahat. This research has used the quantitative approach where the questionnaire has been distributed to 36 volunteers at Civil defense of Batu Pahat, Johor. Data has been collected has been analyzed using Statistical Package for Social Science (SPSS) version 24.0. Based on the finding, there has been a significant relationship between workplaces spirituality and leadership effectiveness.  The workplace spirituality has given a positive effect on the leadership effectiveness in Civil Defense of Batu Pahat, Johor. The data has been collected can helps civil defense and also the leader itself.